Interconnections between Social and Economic Indicators in the Context of EU Resilience: Array - Ailincă, Alina Georgeta (Acta Universitatis Danubius. Œconomica, 2022)
The COVID 19 pandemic has once again exposed a number of important risks and problems for the world's economies. Although the present analyzes in the literature are more and more often aggregated between fields, emphasizing the capacity of digitalization and international relations to improve the transition to the circular economy, resilience speaks not only of positive aspects but also of vulnerabilities. Thus, the article deals with the link between vulnerabilities and capacities of the socio-economic domain at EU27 level. The study uses Eurostat data for the period 2011-2020, systematized in the panel form. The results once again demonstrate the need to strengthen public support for health and education, for research and development, in order to reduce socio-economic vulnerabilities at EU27 level, demonstrating the need to correlate policy efforts with results.